2016
DOI: 10.1108/medar-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Social responsibility disclosure in the international gambling industry: a research note

Abstract: Purpose This paper aims to explore the extent to which social responsibility and social and environmental reporting and disclosure have any relevance in the (so-called) controversial industries. The literature is ambivalent over the extent to which it is expected to see corporate social responsibility and social disclosure employed as active legitimation strategies. However, the apparent importance of “responsible gambling” in both the literature and in gambling industry initiatives suggests, at least a priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 40 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…Prior studies have reported a substantial increase in the level of social disclosure after major incidents in both developed countries (Patten, 1991(Patten, , 1992Deegan et al, 2000;Deegan et al, 2002;Cho, 2009) and developing countries (De Villiers and Van Staden, 2006;Islam and Mathews, 2009;Coetzee and Van Staden, 2011;Islam and Islam, 2011), but the five observed state-owned enterprises appeared to have a rather different disclosure behavior. Although the findings appeared contrary to the conventional view, they have exhibited a disclosure pattern similar to the organizations examined in a few studies in the prior literature (Solomon and Lewis, 2002;Campbell et al, 2003;Tilling and Tilt, 2010;Leung and Gray, 2015). Such a decreasing disclosure pattern suggested that the Chinese companies may have perceived the sensitive information about the train accident to be potentially harmful rather than useful to repair or maintain their legitimacy.…”
Section: Observations and Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Prior studies have reported a substantial increase in the level of social disclosure after major incidents in both developed countries (Patten, 1991(Patten, , 1992Deegan et al, 2000;Deegan et al, 2002;Cho, 2009) and developing countries (De Villiers and Van Staden, 2006;Islam and Mathews, 2009;Coetzee and Van Staden, 2011;Islam and Islam, 2011), but the five observed state-owned enterprises appeared to have a rather different disclosure behavior. Although the findings appeared contrary to the conventional view, they have exhibited a disclosure pattern similar to the organizations examined in a few studies in the prior literature (Solomon and Lewis, 2002;Campbell et al, 2003;Tilling and Tilt, 2010;Leung and Gray, 2015). Such a decreasing disclosure pattern suggested that the Chinese companies may have perceived the sensitive information about the train accident to be potentially harmful rather than useful to repair or maintain their legitimacy.…”
Section: Observations and Discussionmentioning
confidence: 61%
“…Tilling and Tilt's (2010) analysis showed that the social disclosure of Rothmans Limited, the Australian-based tobacco company, had decreased over time when they were faced with a threat. Furthermore, Leung and Gray (2015) found that there was little disclosure in relation to responsible gambling in the gambling industry. As a result, these studies may not be in line with the mainstream CSR disclosure literature.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…Massa et al (2015) discusses the mechanisms and consequences involved in developing a sustainability report for a small to medium enterprise. Leung and Gray (2016) explore the relevance of social responsibility and social and environmental reporting to controversial industries. Borghei, Leung and Guthrie (2016) explore voluntary greenhouse gas disclosures after the introduction of the National Greenhouse and Energy Reporting Act 2007 and before the introduction of the Australian ETS.…”
Section: Accounting Education (Ed)mentioning
confidence: 99%
“…Studies also express addressing knowledge gaps in current literature (Barac et al 2016;Huang et al 2015;Leung & Gray 2016), and develop theories (Ram et al 2016). Suggestions for future research are also common (Free 2015;Siboni et al 2016).…”
Section: Accounting Education (Ed)mentioning
confidence: 99%
“…Therefore, it appears that the responsible provision of gambling services and its advertising has become an important part of the image of online bookmakers, with companies now beginning to recognise that demonstrating responsibility can aid the longer term sustainability of their business (Soriano et al 2012). However, Leung and Gray (2016) maintain that there is an inverse relationship between the size of gambling firms and their level of social responsibility disclosure.…”
Section: Introductionmentioning
confidence: 99%